Mammal type specimens in the Macleay Collections, University of Sydney - Parnaby, Harry; Gill, Anthony C. (Zootaxa, 2021)
Type material of 12 mammal taxa originally proposed as species or subspecies are housed in the former Macleay Museum (now Macleay Collections, Chau Chak Wing Museum), University of Sydney and consist of seven holotypes and 12 syntypes. These were published from 1875 to 1887, five by N.N. Miklouho-Maclay and seven by E.P. Ramsay, of which six are currently considered valid taxa. Six type specimens are identified in the Collection for the first time. This includes rediscovery of the holotype skull of the New Guinean forest wallaby Dorcopsis chalmersii Miklouho-Maclay not reported since its description in 1884, a likely syntype of the bandicoot Perameles macroura torosa Ramsay, and three additional syntypes of the flying fox Pteropus (Epomops?) epularius Ramsay. The holotype of the dasyurid Antechinus (Podabrus) froggatti Ramsay, housed at the Australian Museum since before 1959, is also discussed. Limited specimen data currently prevents validation of an additional six specimens identified here as suspected syntypes of four further names: the macropodoids Halmaturus mastersii Krefft, Halmaturus crassipes Ramsay and Hypsiprymnodon moschatus Ramsay, and the bandicoot Perameles moresbyensis Ramsay. Individual accounts are given for a total of 21 proposed names. Type material of four of these remain unlocated in world collections and it is not known if they were ever in the Macleay Collections: the bandicoot Brachymelis garagassi Miklouho-Maclay, 1884; the wallaby Macropus tibol Miklouho-Maclay, 1885; the cuscus Cuscus chrysorrhous var. goldiei Ramsay and the giant rat Hapalotis papuanus Ramsay. The nomenclatural status of the possum Phalangista pinnata Ramsay, 1877, a possible nomen nudum, is also discussed. No nomenclatural actions are taken in this paper.